Elastin Insufficiency Confers Proximal and Distal Pulmonary Vasculopathy in Mice, Partially Remedied by the KATP Channel Opener Minoxidil: Considerations and Cautions for the Treatment of People With Williams-Beuren Syndrome - Knutsen, Russell H.; Gober, Leah M.; Kronquist, Elise K.; Kaur, Maninder; Donahue, Danielle R.; Springer, Danielle; Yu, Zu Xi; Chen, Marcus Y.; Fu, Yi-Ping; Choobdar, Feri; Nguyen, My-Le; Osgood, Sharon; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Williams Beuren syndrome (WBS) is a recurrent microdeletion disorder that removes one copy of elastin (ELN), resulting in large artery vasculopathy. Early stenosis of the pulmonary vascular tree is common, but few data are available on longer-term implications of the condition. Methods: Computed tomography (CT) angiogram (n=11) and echocardiogram (n=20) were performed in children with WBS aged 3.4-17.8 years. Controls (n=11, aged 4.4-16.8 years) also underwent echocardiogram. Eln+/- mice were analyzed by invasive catheter, echocardiogram, micro-CT (CT), histology, and pressure myography. We subsequently tested whether minoxidil resulted in improved pulmonary vascular endpoints. Results: WBS participants with a history of main or branch pulmonary artery (PA) stenosis requiring intervention continued to exhibit increased right ventricular systolic pressure (RVSP, echocardiogram) relative to their peers without intervention (p<0.01), with no clear difference in PA size. Untreated Eln+/- mice also show elevated RVSP by invasive catheterization (p<0.0001), increased normalized right heart mass (p<0.01) and reduced caliber branch PAs by pressure myography (p<0.0001). Eln+/- main PA medias are thickened histologically relative to Eln+/+ (p<0.0001). Most Eln+/- phenotypes are shared by both sexes, but PA medial thickness is substantially greater in Eln+/- males (p<0.001). Eln+/- mice showed more acute proximal branching angles (p<0.0001) and longer vascular segment lengths (p<0.0001) (CT), with genotype differences emerging by P7. Diminished PA acceleration time (p<0.001) and systolic notching (p<0.0001) were also observed in Eln+/- echocardiography. Vascular casting plus CT revealed longer generation-specific PA arcade length (p<0.0001), with increased PA branching detectable by P90 (p<0.0001). Post-weaning minoxidil decreased RVSP (p<0.01) and normalized PA caliber (p<0.0001) but not early-onset proximal branching angle or segment length, nor later-developing peripheral branch number. Conclusions: Vascular deficiencies beyond arterial caliber persist in individuals with WBS who have undergone PA stenosis intervention. Evaluation of Eln+/- mice reveals complex vascular changes that affect the proximal and distal vasculatures. Minoxidil, given post-weaning, decreases RVSP and improves lumen diameter, but does not alter other earlier-onset vascular patterns. Our data suggest additional therapies including minoxidil could be a useful adjunct to surgical therapy, and future trials should be considered.